Species composition and diversity of waterbird communities in Important Bird and Biodiversity Area (IBA) of South West Johor Coast, Malaysia - NUR ATHIRAH FAUZI; KAVIARASU MUNIAN; AHMAD KHUSAINI MOHD KHARIP SHAH; NOR ATIQAH NORAZLIMI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Fauzi NA, Munian K, Shah AKMK, Norazlimi NA. 2023. Species composition and diversity of waterbird communities in Important Bird and Biodiversity Area (IBA) of South West Johor Coast, Malaysia. Biodiversitas 24: 3471-3480. Mangroves play a crucial role in supporting intertidal flats and providing habitats that enrich benthic communities, which in turn serve as feeding grounds for coastal waterbirds. However, the degradation of mangrove habitats caused by coastal reclamation activities indirectly impacts prey availability and, consequently, the populations of waterbirds. The coastline habitat along the Important Bird and Biodiversity Area (IBA) of the South West Johor Coast is currently under threat due to new and ongoing development projects involving large-scale reclamation activities. Therefore, this research was conducted to study the diversity and abundance of waterbirds and their relationship with prey availability. The study was conducted in three coastal mudflat sites along the South West Johor Coast, namely Tanjung Piai, Pontian Kechil, and Muar, from November 2020 to May 2021. The direct observation technique was used to determine the abundance of waterbirds, while the benthic core sampling method was employed to assess prey availability in all study sites. In total, 3,717 individual waterbirds, comprising 17 species, were counted across the three study sites. The study confirmed a significant positive relationship between the abundance of waterbirds and prey availability (R2=0.501). The results of this study serve as important baseline data and references for the conservation of waterbirds along the South West Johor Coast. Through the study, we believe that the relevant authorities are able to formulate sound conservation strategies to preserve the habitat for a vast diversity of waterbirds.